Assembly mechanisms, not species pool, shape β-diversity of soil methanotrophic communities in steppes of China - Kou, Yongping; Feng, Zhe; Li, Huan; Liu, Yanjiao; Xu, Lin; Li, Xiangzhen (Frontiers in Microbiology, 2025)
IntroductionOne of the central aims in ecology is elucidating the mechanisms that shape community diversity. While biodiversity patterns across geographical gradients are often attributed both to local assembly processes and regional species pools, the distinct roles of these factors in shaping soil aerobic methanotrophic diversity remain underexplored.MethodsUsing amplicon sequencing and bioinformatics analysis, this study focuses on comparing the relative importance of species pool and community assembly processes in shaping soil methanotrophic communities across three distinct plateaus in China: the Loess Plateau, the Qinghai-Tibetan Plateau, and the Inner Mongolian Plateau. Each of these plateaus includes three distinct steppe habitats: desert, meadow, and typical steppe.ResultsOur findings reveal that pmoA beta (β)-diversity followed a distance-decay pattern, which declined with geographical distance at different rates depending on the steppe type and area, potentially due to diverse mechanisms of community assembly. Moreover, a decoupling between β-diversity and gamma-diversity observed, suggesting that local community assembly mechanisms primarily account for variations in β-diversity patterns. Furthermore, the relative significance of these assembly processes (e.g., dispersal limitation, drift, environmental filtering, and biotic interactions) varies according to spatial scales and steppe types. Notably, the differential environmental conditions (such as soil pH, yearly average temperature, and precipitation) across scales and steppe habitats primarily modulate the intensity of these assembly processes, thereby influencing β-diversity.ConclusionIn summary, our study emphasizes the crucial role of local community assembly in changing soil methanotrophic β-diversity’s geographical patterns, highlighting the significance of a nuanced understanding of these processes for effective conservation and management strategies.